Effect of intenal heat generation on marangoni convection in a fluid saturated porous medium. - Mohd Mokhtar, Nor Fadzillah; Md. Arifin, Norihan; Nazar, Roslinda; Ismail, Fudziah; Suleiman, Mohamed (CESER Publications, 2010)
Linear stability analysis is applied to investigate the effect of internal heat generation on Marangoni convection in a fluid saturated porous medium bounded below by a insulating rigid surface and above by a non-deformable free surface. The Darcy law and the Brinkman model are used to describe the flow in the porous medium heated from below. The conditions for the onset of instability occurring via steady convective modes are solved exactly. The asymptotic solution of the long wavelength is also obtained using regular perturbation technique with wave number as a perturbation parameter. It is observed that the critical Marangoni number decreases with an increase in the dimensionless heat source strength.